Design and Development of an IoT-Based Instructional Teaching Aid to Support Embedded Systems Learning - Rahardjo, Sugeng Budi; Ambarwati, Intan; Hisniati, Sally Badriya (CV. Tripe Konsultan, 2026)
Embedded systems education requires hands-on learning tools that enable students to understand real-time data acquisition, sensor integration, and network-based control. However, laboratory limitations and the lack of contextual teaching media often hinder effective learning. This study aims to design and develop an Internet of Things (IoT)-based teaching aid to support embedded systems learning using a real-world case study of water quality monitoring in tilapia aquaculture. The teaching aid integrates pH, temperature, turbidity, and Total Dissolved Solids (TDS) sensors with an ESP32 microcontroller and a cloud-based IoT platform (Blynk) to enable real-time monitoring and notification features. A research and development approach using a prototyping method was employed. Functional testing and classroom-based trials indicate that the teaching aid operates reliably, provides real-time feedback, and enhances students’ understanding of embedded system concepts, including sensor calibration, data processing, and IoT communication. The results suggest that IoT-based teaching aids grounded in real-world applications can significantly improve experiential learning in embedded systems education.